Do MEB ao CESEP : uma análise da educação popular em Sergipe - Rodrigues, Gessica Santana (2016)
This study aims to analyze how the question of popular education builds and develops the political and social scene of the Sergipe state, comprising the different contexts and dynamics that made possible the composition of a scene of protests and engagement around the cause. As methodological theoretical framework, the study's emphasis on an analysis of the construction of the cause as a public problem, tying up the analysis of network relations and militant trajectories. Thus, research is developed from the 1960s to the 2000s, dividing into three stages: the first refers to the construction process of the cause, when are the first organizations around the same, as the MEB and the CPC. The second time sets up a "reframing cause" going to be a more strategic and political movement born in this context the CESEP, emerging new actors and new dynamics of the cause. Already in the 2000s, observed a "fragmentation of the case", it becomes incorporated with other agendas, particularly the solidarity economy. Thus, we see how different contexts formulate different networks relationship around the cause, being articulated personal and impersonal relations in alliances. We also observed that at first the relations pervade the work of the Church, as in the second time the relationships were more branched and heterogeneous. Beyond this perspective the research raises, from the militant trajectories, two profiles of careers around the cause: multiple religious and militant activism. This reinforces the argument of the influence of political and social contexts in social action dynamics. Thus, the study seeks to bring contributions to the field of sociology of social movements. Housed in an analysis that gives rise to the case studies, the actors involved and assigned meanings, the research raises questions to better understand the Sergipe and even Brazilian politics.